Doctors' self-reported physical activity, their counselling practices and their correlates in urban Trivandrum, South India: should a full-service doctor be a physically active doctor?. Issue 6 (14th June 2013) - Patra, Lipika; Mini, G K; Mathews, Elezebeth; Thankappan, K R
Abstract : Background: Doctors' self-reported physical activity (PA) is associated with their propensity for prescribing PA. Methods: We surveyed 146 doctors (median age 42 years; men 58.9%), selected by multistage random sampling. Information on demographic details, self-reported PA and counselling offered to their patients was collected using a pretested, structured, self-administered questionnaire. Multivariate logistic regression analysis was carried out to find the predictors of PA and PA counselling offered to the patients. Results: Moderate PA was reported by 37.7% (95% CI 29.8 to 45.5) of the doctors and the remaining 62.3%reported being inactive. Doctors who were motivated to perform PA (OR 4.01, 95% CI 1.82 to 8.86), who used exercise equipment at home (OR 3.97, CI 1.68 to 9.36) and who used a neighbourhood facility for PA (OR 2.36, CI 1.11 to 5.02) were more likely to perform moderate PA compared with their counterparts. 25% of the doctors always asked and advised their patients on PA. Doctors who believed that their own healthy lifestyle influenced advice practices (OR 9.13, CI 2.49 to 33.41), who consulted less than 30 patients/day (OR 5.35, CI 1.41 to 20.25) and who reported previous participation in sports activities (OR 4.22, CI 1.77 to 10.04) were more likely to always ask and advise their patients on PA compared with their counterparts. Conclusions: A majority of the doctors in our study were inactive and did not ask or advise their patients on PA. Measures are warranted to enhance doctors' own PA and their counselling practices.